Low-Dose Oxygen Enhances Macrophage-Derived Bacterial Clearance following Cigarette Smoke Exposure. (14th June 2016) - Bain, William G.; Tripathi, Ashutosh; Mandke, Pooja; Gans, Jonathan H.; D'Alessio, Franco R.; Sidhaye, Venkataramana K.; Aggarwal, Neil R.
Abstract : Background. Chronic obstructive pulmonary disease (COPD) is a common, smoking-related lung disease. Patients with COPD frequently suffer disease exacerbations induced by bacterial respiratory infections, suggestive of impaired innate immunity. Low-dose oxygen is a mainstay of therapy during COPD exacerbations; yet we understand little about whether oxygen can modulate the effects of cigarette smoke on lung immunity. Methods. Wild-type mice were exposed to cigarette smoke for 5 weeks, followed by intratracheal instillation of Pseudomonas aeruginosa (PAO1) and 21% or 35–40% oxygen. After two days, lungs were harvested for PAO1 CFUs, and bronchoalveolar fluid was sampled for inflammatory markers. In culture, macrophages were exposed to cigarette smoke and oxygen (40%) for 24 hours and then incubated with PAO1, followed by quantification of bacterial phagocytosis and inflammatory markers. Results. Mice exposed to 35–40% oxygen after cigarette smoke and PAO1 had improved survival and reduced lung CFUs and inflammation. Macrophages from these mice expressed less TNF-α and more scavenger receptors. In culture, macrophages exposed to cigarette smoke and oxygen also demonstrated decreased TNF-α secretion and enhanced phagocytosis of PAO1 bacteria. Conclusions. Our findings demonstrate a novel, protective role for low-dose oxygen following cigarette smoke and bacteria exposure that may be mediated by enhanced macrophage phagocytosis.